Economic Impact in Waste Recycling Activities by the Waste Bank Community Group in Tanjung Siambang, Dompak - Vistin Gulo; Siti Arieta; Sachi Emelin Carissa (Formosa Journal of Science and Technology, 2023)
The waste problem in Tanjungpinang City, Riau Islands Province from April 29th to May 8th 2022 reached 315, 27 tons of garbage. While the waste produced by the community reached 827,570 tons and the average per day of the waste generated by the people and residents of Tanjungpenang reached 114.2 tons. The goal is to reduce the amount of garbage dumped, by the actions of the people themselves to clean up and increase revenue. The methods used are observations, interviews and documentation. This waste management can be beneficial to managers and customers as well as the surrounding community. So the conclusion of this research is that the garbage that damages the marine ecosystem nor this environment can bring benefits of economic, social, environmental value that can add to the income of Tanjung Siambang, Dompak.